Occupational therapists’ experiences of working with people with dementia: a qualitative study - Johannes Österholm; Åsa Larsson Ranada (Scandinavian Journal of Occupational Therapy)
Background Dementia is an age-related disease associated with complex health and care needs. Due to demographical shifts, the number of older people with dementia is forecasted to increase. Occupational therapists encounter people with dementia in their daily work, yet little is known about their experience of working with people with dementia.Aim/objectives To explore occupational therapist’s experiences of working with people with dementia.Material and methods Ten occupational therapists were interviewed using semi-structured interviews. Data were analysed using reflexive thematic analysis.Results The results are presented in five different themes: Working with persons who do not recognise decline in their abilities; Saving-face of the person in assessment situations; Facilitating continued engagement in everyday activities; Utilising information provided by care staff; Balancing different preferences on how to proceed.Conclusion Occupational therapists perceive a need in their work to employ various face-saving strategies and facilitate engagement in everyday activities. The results are exploratory and additionally research is needed to understand the therapists’ experiences of working with persons with dementia.Significance Everyday activities should be tailored to the person’s abilities, with an emphasis on facilitating the person in carrying them out rather than the social environment taking them over.